2018
DOI: 10.18203/2320-6012.ijrms20180288
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of ondansetron and granisetron in combination with dexamethasone-in prophylaxis for postoperative nausea and vomiting (PONV) in laproscopic cholecystectomies

Abstract: INTRODUCTIONPost operative nausea and vomiting (PONV) is the most common and distressing symptom experienced by surgical patients. The incidence of PONV is 20-30 % in general anaesthesia.1,2 The incidence of PONV is 70-80% in females, and more in ocular, middle ear, gynecological surgeries and laproscopic procedures.2 Without antiemetic prophylaxis, the incidence 50-70% in laproscopic cholecystectomies. PONV causes harm to surgical site sutures, anastomoses.3 It increases intraocular, intra-cranial pressure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Granisetron is used primarily for post-operative nausea and vomiting prophylaxis or treatment, and many previously published studies support our results in this aspect. Nanjundaswamy et al concluded that both granisetron and ondansetron combined with dexamethasone were effective in reducing nausea and vomiting incidences in laparoscopic cholecystectomy surgery patients [20]. Daria and Kumar reported that for patients undergoing gynecologic laparoscopic surgery under general anesthesia, granisetron alone had a lower success rate in the prevention of post-surgery nausea and vomiting compared to a combination of granisetron and dexamethasone [21].…”
Section: Discussionmentioning
confidence: 99%
“…Granisetron is used primarily for post-operative nausea and vomiting prophylaxis or treatment, and many previously published studies support our results in this aspect. Nanjundaswamy et al concluded that both granisetron and ondansetron combined with dexamethasone were effective in reducing nausea and vomiting incidences in laparoscopic cholecystectomy surgery patients [20]. Daria and Kumar reported that for patients undergoing gynecologic laparoscopic surgery under general anesthesia, granisetron alone had a lower success rate in the prevention of post-surgery nausea and vomiting compared to a combination of granisetron and dexamethasone [21].…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be because they have not taken APFEL score into consideration which is an important confounding factor in case of PONV and all their patients arefemales. 11 Moussa AA et al, conducted a study on 120 patients undergoing laparoscopic bariatric surgery. Patients were randomized in 4 groups receiving either granisetrone 1 mg, granisetrone 1 mg plus droperidol 1.25 mg, granisetrone 1 mg plus dexamethasone 8 mg or placebo immediately before induction of anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…The traditional antiemetics include antihistamines, anticholinergics and dopamine-receptor antagonists [3]. Newer drugs like Serotonin Receptor Antagonists (granisetron and ondansetron) provide better efficacy and safety as compared to the traditional drugs [4]. They bind to the 5-Hydroxytryptamine subtype-3 (5HT3) receptors, selectively blocking the emetogenic stimuli during anesthesia and surgery.…”
Section: Introductionmentioning
confidence: 99%